Factors Affecting Audit Delay - Sudirman, Ganefo; Mahwiyah, Mahwiyah (Sean Institute, 2024)
This study aims to determine the factors influencing audit delay, including company size, profitability, size of the public accounting firm, and debt to equity ratio. The data used in this research consists of annual reports from manufacturing companies in the food and beverage industry sector listed on the Indonesia Stock Exchange during the period 2017-2020. This study employs a quantitative method and utilizes multiple linear regression analysis using IBM SPSS 23. The implications of this research are expected to provide positive contributions to various stakeholders. For companies, it can serve as consideration in completing audit reports. Internal auditors can also focus on maintaining audit quality and integrity. Additionally, this study is beneficial for investors and potential investors in assessing opportunities for increasing stock value in manufacturing companies within the food and beverage industry sector listed on the IDX. Regulators can evaluate and monitor indications of any fraud in the audit completion process. Therefore, both the company's financial statements and external auditors must collaboratively complete the audited financial reports. The research findings indicate that company size and debt to equity ratio do not influence audit delay, while profitability and the size of the public accounting firm significantly affect audit delay.